Differentiated Learning Models Based on Students’ Talents and Interests for Inclusive Education in the Context of Globalized Learning Environments - Dedi Gunawan Saputra; Sri Suharti (International Forum of Researchers and Lecturers, 2024)
This study examines the impact of differentiated learning models in inclusive educational settings, focusing on their effect on student participation, motivation, and academic performance. Differentiated instruction (DI) adapts content, teaching methods, and assessments to meet the diverse learning styles, interests, and abilities of students. Using a mixed methods approach, the research combines quantitative and qualitative data to explore how DI influences engagement and academic outcomes in diverse classrooms. The findings show that DI significantly increased student participation, as lessons tailored to individual strengths encouraged more active involvement. Motivation also improved, with students displaying higher intrinsic motivation when engaging with relevant material at their own pace. Additionally, academic performance improved, especially for students who had struggled with traditional teaching methods. These results suggest that DI is an effective strategy for inclusive education, particularly for students with special educational needs and disabilities (SEND). The study emphasizes the importance of teacher training and ongoing professional development for successful DI implementation. The implications are significant for global educational settings, where classrooms are becoming more diverse. By adopting differentiated strategies, educators can create more equitable and inclusive learning experiences. Future research should explore the long-term effects of DI in various cultural and educational contexts.